Book Reviews (Journal of Finance, 1991)
Book reviewed in this article: A Bibliography of Finance . By RICHARD BREALEY and HELEN EDWARDS. Cambridge, MA: The MIT Press, 1991. Pp. xli + 822. Modern Corporate Finance . By ALAN C. SHAPIRO. New York, NY: Macmillan Publishing Company, 1990. Pp. xxvi + 1045. Options: An Introduction . By ROBERT W. KOLB. Miami, FL: Kolb Publishing Co., 1991. Pp. viii + 216. The Separation of Commercial and Investment Banking: The Glass‐Steagall Act Revisited and Reconsidered . By GEORGE J. BENSTON. Oxford: Oxford University Press, 1990. Pp. x + 263.